2014
DOI: 10.1002/ajhb.22583
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of body composition components and soft‐tissue biochemical factors to genetic variation of body mass index (BMI) in an ethnically homogeneous population

Abstract: This study clearly suggests that FM and FFM contributed almost equally to BMI variation, and provides evidence that this contribution is caused by common genetic as well as shared environmental and metabolic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Women have higher adiponectin concentrations due at least in part to the adiponectionlowering effects of testosterone (Berra et al, 2006). Whereas sex-differences in adiponectin concentrations are consistently reported (Liu et al, 2008;Hicks et al, 2007;Comuzzie et al, 2001;Vaughan et al, 2015;Chuang et al, 2004;Dosaev, Prakash & Livshits, 2014;Henneman et al, 2010;Guo et al, 2006;Ling, Waterworth et al, 2009;Vasseur et al, 2002;Cesari et al, 2007), sex-differences in their heritabilities are not. This we attribute to their reliance on statistical procedures that require normally distributed data and logarithmic or other data transformations.…”
Section: Discussionmentioning
confidence: 99%
“…Women have higher adiponectin concentrations due at least in part to the adiponectionlowering effects of testosterone (Berra et al, 2006). Whereas sex-differences in adiponectin concentrations are consistently reported (Liu et al, 2008;Hicks et al, 2007;Comuzzie et al, 2001;Vaughan et al, 2015;Chuang et al, 2004;Dosaev, Prakash & Livshits, 2014;Henneman et al, 2010;Guo et al, 2006;Ling, Waterworth et al, 2009;Vasseur et al, 2002;Cesari et al, 2007), sex-differences in their heritabilities are not. This we attribute to their reliance on statistical procedures that require normally distributed data and logarithmic or other data transformations.…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation of this strategy of adjusting for fat mass is that the ability to identify genetic signals with an impact on both lean mass and fat mass will be reduced. Some studies suggested lean mass and fat mass have a substantial genetic correlation (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been obtained for leptin [ 17 19 ]. To better elucidate the role of adipocytokines in the development of insulin resistance and diabetes, it is thus critical to investigate the associations of adiponectin and leptin with insulin resistance because most previous studies have focused on evaluating the associations of these adipocytokines with obesity and diabetes [ 14 , 20 , 21 ]. Therefore, the present study sought to examine the associations of serum adiponectin and leptin with β-cell function and insulin resistance among a large sample of the rural Chinese population whose prevalence rates of overweight and obesity are substantially lower than those of Western populations largely due to differences in dietary and lifestyle factors [ 22 ].…”
Section: Introductionmentioning
confidence: 99%